Cross-Cultural Comparative Literature as a Pedagogical Strategy in Advanced BIPA Classes - Ayu Puspa Nanda; Helvy Tiana Rosa; Muhamad Fajar Rizkia; Rahmi Yulia Ningsih; Sifa Awalunisa Al Mugni (Badan Pengembangan dan Pembinaan Bahasa, 2026)
Teaching Indonesian to Foreign Speakers (BIPA) at the advanced level requires teaching strategies that focus not only on language proficiency but also on developing cultural competence and the courage to express oneself. This article examines the application of a cross-cultural comparative literature approach through the medium of folktales and poetry as a pedagogical strategy in teaching advanced BIPA. This study uses a reflective qualitative approach based on teaching experiences at Multimedia Nusantara University. This study involved a total of 10 subjects. The majority of the subjects came from South Korea, while the remaining came from Japan and Thailand. Data collection was conducted through participatory observation, audiovisual documentation in the form of storytelling and poetry reading activities, and learner portfolios. The results show that this strategy can significantly improve cultural awareness, learning motivation, courage to express oneself, and expressive language competence among BIPA learners. By using the cultural background and literary experiences of BIPA learners as a starting point, literature acts as an affective and cultural bridge that facilitates dialogic and meaningful learning. These findings offer a new pedagogical perspective in BIPA teaching that is oriented towards strengthening identity and cross-cultural literacy. Abstrak Pengajaran Bahasa Indonesia untuk Penutur Asing (BIPA) di tingkat lanjut memerlukan strategi pengajaran yang tidak hanya berfokus pada kemahiran berbahasa, tetapi juga pada pengembangan kompetensi budaya dan keberanian untuk mengekspresikan diri. Artikel ini mengkaji penerapan pendekatan sastra bandingan lintas budaya melalui media cerita rakyat dan puisi sebagai strategi pedagogis dalam pengajaran BIPA tingkat lanjut. Penelitian ini menggunakan pendekatan kualitatif reflektif berdasarkan pengalaman mengajar di Universitas Multimedia Nusantara. Penelitian ini melibatkan total 10 subjek. Mayoritas subjek berasal dari Korea Selatan, sedangkan sisanya berasal dari Jepang dan Thailand. Pengumpulan data dilakukan melalui observasi partisipatif, dokumentasi audiovisual dalam bentuk kegiatan bercerita dan pembacaan puisi, serta portofolio pembelajar. Hasil penelitian menunjukkan bahwa strategi ini secara signifikan dapat meningkatkan kesadaran budaya, motivasi belajar, keberanian berekspresi, serta kompetensi berbahasa ekspresif pada pembelajar BIPA. Dengan menggunakan latar belakang budaya dan pengalaman sastra pembelajar BIPA sebagai titik tolak, sastra berperan sebagai jembatan afektif dan budaya yang memfasilitasi pembelajaran yang dialogis dan bermakna. Temuan ini menawarkan perspektif pedagogis baru dalam pengajaran BIPA yang berorientasi pada penguatan identitas dan literasi lintas budaya.